2010
DOI: 10.1089/jop.2009.0135
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Myopia Onset with 0.025% Atropine in Premyopic Children

Abstract: Regular topical administration of 0.025% atropine eye drops can prevent myopia onset and myopic shift in premyopic schoolchildren for a 1-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
86
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 27 publications
2
86
0
3
Order By: Relevance
“…Most prior studies of atropine eyedrops excluded this level of myopia, 12-14 but our results are almost identical to those found by Fang et al using 0.025% atropine in premyopic children. 11 The study found that a slightly stronger concentration of atropine reduced the rate of progression to -0.14 D/year in the treatment group compared with -0.58 D/ year in the control group. 11 Most of our low myopic cases became partially or completely spectacle free compared to worsening myopia in every control subject (Fig.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Most prior studies of atropine eyedrops excluded this level of myopia, 12-14 but our results are almost identical to those found by Fang et al using 0.025% atropine in premyopic children. 11 The study found that a slightly stronger concentration of atropine reduced the rate of progression to -0.14 D/year in the treatment group compared with -0.58 D/ year in the control group. 11 Most of our low myopic cases became partially or completely spectacle free compared to worsening myopia in every control subject (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…1,3,9 Current research is focused on decreasing the severity of myopia and possibly preventing its onset entirely. 10,11 Many treatments have been advocated to slow myopic progression: atropine eyedrops of varying concentrations, [12][13][14] pirenzepine 2% gel, 15 deliberate optical undercorrection, 1,16,17 increased outdoor activity and sunlight exposure, [18][19][20] bifocal and progressive eyeglasses, 1,3,21-23 and contact lenses (rigid gas permeable, 24 peripheral defocus, 25 and orthokeratology 26,27 ). Pirenzepine and progressive eyeglasses cause a statistically significant, but clinically small reduction in the rate of myopic progression.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the present report is the first to show atropine 1% effectively retarding early myopia: 93% of patients in the treatment group had reduction in myopia and experienced an improvement in uncorrected distance visual acuity. In the present study, we chose to test myopia of À0.50 D to À2.00 D. After 1 year of atropine treatment, there was a reduction of myopia by 0.32 AE 0.22 D. In the study by Fang and colleagues, 22 although the participants' spherical refraction was À0.31 AE 0.45 D, there was a slight increase in the spherical refraction of atropine-treated subjects. We believe that the this result could be explained by the low concentration of atropine (0.025%)-perhaps too low to develop the full effect.…”
Section: Discussionmentioning
confidence: 95%
“…To date, atropine eyedrops are still the only treatment demonstrated to have a consistent effect on the retardation of myopia progression. [21][22][23][24] Although there have been multiple reports about the effect of atropine in the treatment of myopia progression, most studies include moderate or high myopic or premyopic patients. To our knowledge, the present report is the first to show atropine 1% effectively retarding early myopia: 93% of patients in the treatment group had reduction in myopia and experienced an improvement in uncorrected distance visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that regular topical administration of 0.025% atropine eye drops can prevent myopia onset and myopic shift in premyopic school children for a 1-year period (10).…”
Section: Introductionmentioning
confidence: 99%